2012
DOI: 10.1259/dmfr/85015314
|View full text |Cite
|
Sign up to set email alerts
|

CT findings in two cases of lobular capillary haemangioma of the nasal cavity: focusing on the enhancement pattern

et al.

Abstract: Lobular capillary haemangioma, known as pyogenic granuloma, is a relatively common benign vascular neoplasm that is composed of hyperplastic clusters of capillaries arranged in a lobular architectural pattern. Most mucosal lobular capillary haemangioma (LCH) of the head and neck arise in the oral cavity, but the nasal cavity involvement is rare. We report here on the CT imaging findings of two cases of LCH involving the nasal cavity, with an emphasis being placed on the different pattern of enhancement of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The first description of Lobular capillary haemangiomas was in 1897 by Poncet A CT scan without contrast enhancement should show a well-defined soft-tissue mass able to undergo intense enhancement on postcontrast study [25]. Generally, bony erosion is not associated with lobular nasal capillary haemangiomas, though a few studies do find this symptom to be a characteristic [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first description of Lobular capillary haemangiomas was in 1897 by Poncet A CT scan without contrast enhancement should show a well-defined soft-tissue mass able to undergo intense enhancement on postcontrast study [25]. Generally, bony erosion is not associated with lobular nasal capillary haemangiomas, though a few studies do find this symptom to be a characteristic [26].…”
Section: Discussionmentioning
confidence: 99%
“…The most common presenting symptoms of CH of the nasal cavity include recurrent unilateral epistaxis and nasal obstruction; facial pain, alteration of smell, and headache are seldom observed [25]. At endoscopy, the lesion usually appears as a single hypervascularized mass of a red to purple color, not exceeding 1 cm, and with a predilection for the anterior portion of the nasal septum.…”
Section: Discussionmentioning
confidence: 99%
“…In the residual cases (16.7 %), CT findings consisted of a lobular, intensely enhancing mass and a hypoattenuating area containing linear and spotty enhancing foci. Some believe that the degree of enhancement of the tumour on the CT scans is not constant, probably due to the variable size of both the tumour and vessels [14]. LCH was not thought to be universally associated with bony erosion though a few studies have found bony erosion to be more common [15].…”
Section: Discussionmentioning
confidence: 99%
“…MRI demonstrates T1 hypointensity and T2 hyperintensity in LCH. Bone erosion in LCH is mainly due to compressive devascularisation by the tumour 1 2 5 9 10. Angiography reveals the presence of increased vascularity due to the extensive feeding vessels to the tumour 3…”
Section: Discussionmentioning
confidence: 99%